2009
DOI: 10.1002/jcla.20303
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolidase activity and oxidative status in patients with bronchial asthma

Abstract: Asthma is a disease where there is an accumulation of collagen in the reticular basal membrane of the airway leading to chronic inflammation. The enzyme prolidase plays an important role in the breakdown of collagen and the breakdown of intracellular protein especially in the final stage when peptides and dipeptides contain a high level of proline. To evaluate the relationship between prolidase activity and oxidative status in asthma patients. Comparison was made between 42 patients diagnosed with bronchial as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
2
35
3
1
Order By: Relevance
“…In addition to collagen turnover, oxidative status and oxidative stress have also been shown to correlate with prolidase activity levels under certain conditions (Aslan et al. 2007; Cakmak et al. 2009, 2010; Selek et al.…”
Section: Prolidase As a Marker For Diseasementioning
confidence: 99%
“…In addition to collagen turnover, oxidative status and oxidative stress have also been shown to correlate with prolidase activity levels under certain conditions (Aslan et al. 2007; Cakmak et al. 2009, 2010; Selek et al.…”
Section: Prolidase As a Marker For Diseasementioning
confidence: 99%
“…However, conflicting results also have been published. In a recent article published in this journal, Cakmak et al reported that SPA concentrations were lower in asthma patients than in controls (20). Similarly, Myara et al found higher plasma prolidase levels in only 5 of 27 cirrhosis patients; they also failed to identify any correlation between the degrees of fibrosis and prolidase activity.…”
Section: Discussionmentioning
confidence: 97%
“…After an acute injury, the respiratory epithelium is capable of regeneration without remodeling or fibrosis, and in this process, Clara cells proliferate and differentiate into ciliary epithelial cells in bronchioles, as well as in type 2 pneumocyte in alveoli, with maintenance of airway epithelium after injury . It is known that air pollution exposures occurring during the critical periods of lung growth are especially damaging, as well as that the airway epithelium in asthmatics functions abnormally and it is sensitive to oxidative damage . Repeated damage of the airway barrier with agents associated with lowering of serum CC16 during childhood (air pollution, ozone, chlorine metabolites) may increase TH2 response and the penetration of allergens in the lung, which leads to the development of atopic inhalant sensitization …”
Section: Discussionmentioning
confidence: 99%